2022
DOI: 10.22373/psikoislamedia.v7i2.13794
|View full text |Cite
|
Sign up to set email alerts
|

Interest and learning motivation with student participation

Abstract: Many factors affect student participation in the learning process. According to the researcher, two (2) most dominant factors are interest and learning motivation. For that, researchers are interested in proving it empirically. This research aimed to determine the correlation between interest and motivation to learn with student participation. The analysis technique to test the hypothesis by using multiple regression. The data analysis results proved a significant positive relationship between interest and mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In order to develop self-intention and personal significance in the learning process, this internal motivation is typified by making a connection between learning activities and personal interests [10]. Interest and learning motivation are substantially positive, according to the findings of data analysis tests of hypotheses [11]. Studies have shown that students who are interested in a certain discipline have higher learning results and understanding capabilities than those with weak interests [10].…”
Section: Interestmentioning
confidence: 99%
“…In order to develop self-intention and personal significance in the learning process, this internal motivation is typified by making a connection between learning activities and personal interests [10]. Interest and learning motivation are substantially positive, according to the findings of data analysis tests of hypotheses [11]. Studies have shown that students who are interested in a certain discipline have higher learning results and understanding capabilities than those with weak interests [10].…”
Section: Interestmentioning
confidence: 99%